ENGLISH LEARNING EXPRESS SEBAGAI UPAYA MENINGKATKAN MINAT BELAJAR BAHASA INGGRIS MURID SEKOLAH DASAR NEGERI 97 INPRES TELLUMPANUAE KECAMATAN MALLAWA KAB. MAROS, SULAWESI SELATAN - Uyunnasirah Hambali (Abdimas Toddopuli: Jurnal Pengabdian Pada Masyarakat, 2021)
ABSTRACT Learning English at an early age has advantages both biologically and psychologically. Departing from these advantages, the Indonesian government through the Basic Education Curriculum establishes English as a local content that begins to be taught in grade four elementary schools, because English language skills are important enough to be mastered by all levels of society in the global era. In an effort to help make this happen, a community service program in the form of Express English Learning was carried out by training elementary school students in English. This activity was carried out at SDN 97 Inpres Tellumpanuae, Mallawa District, Maros Regency, South Sulawesi. This activity is carried out as an effort to provide English lessons for elementary school students so that they can apply it in every formal and non-formal activity. Besides, this activity is expected to increase students' knowledge and interest, and realize the importance of learning foreign languages, especially English, to increase the nation's competitiveness in the global community. From the results of this activity, it can be concluded that the Express English Learning program can help the primary students gain insight and increase their interest and learning outcomes in learning English. Keywords: Basic English, Express Learning, Learning Interest